A perspective on oil-whirl using two orthogonal coupled oscillators - Brennan, Michael J. [UNESP]; Kamesh, Punithavathy (SAGE Publications, 2016)
It has been known for many years that rotating machinery with hydrodynamic oil-film bearings can exhibit oil-whirl instability, where the unidirectional oil-film force acts on the rotor causing it to vibrate at a natural frequency. In this article, this phenomenon is investigated using two orthogonal coupled oscillators in which the bearing is modeled using short-bearing theory and an oscillating € oil-film to account for cavitation. It is found that at the point of instability, energy is extracted from the oil-film by one of the oscillators, and this energy is dissipated by the other one, such that there is no net energy gain or loss from the system. When the steady-state eccentricity ratio is such that the whirl frequency goes to zero, the oscillators effectively become undamped so that there is no energy exchange between them, and the system is stable.
Keywords: bearings; dynamics; hydrodynamics; industrial machines; Vibration theory